Potensi Nyamuk Sebagai Vektor Di Daerah Endemik Filariasis Kabupaten Bogor, Jawa Barat : Potential of Mosquito as Vectors In Filariasis Endemic Area, Bogor District, West Java - Nirwan, Muhammad; Upik Kesumawati Hadi; Susi Soviana; Surachmi Setyaningsih; Fadjar Satrija (Perkumpulan Entomologi Kesehatan Indonesia, 2024)
Mosquitoe vectors of filariasis must have a long life so that the parasite can complete its life cycle in the mosquito’s body. Mosquitoes with high parity are generally more at risk of transmitting pathogens, as they have made more bites on hosts that have the potential to carry the infection. This study aims to detect the potential of mosquito vectors by calculating the parity number and examining the causative agent in the mosquito’s body. Mosquito parity examination was based on the results of mosquito ovary dissecting during a capture period. Detection of the causative agent was carried out by dissecting tecnique and polymerase chain reaction (PCR). The results showed that the parity rate of mosquitoes caught in Tamansari Village and Cimanggis Village was very high (>80%). Detectionof the causative agent using surgical and PCR methods did not find any L3 larvae and microfilariae in the examined mosquitoes.